PROCEDURE FOR THE DISTRIBUTION OF DIVIDENDS ACCORDING TO LAW 6380/19 - Dahiana Araujo Sandoval, Daisy; Moreno López, Emanuel; Leonarda Perina Martínez, Laura; Enrique Rolón Centurión, Oscar; Ortellado González, Zulma (Revista Gênero e Interdisciplinaridade, 2022)
The objective of this paper is to analyze the procedures to carry out the distribution of dividends according to Law 6380/19 of the Republic of Paraguay. The thematic index of the theoretical foundations is divided into three units: UNIT I: Companies- concepts, types of companies, dividends in a company. UNIT II: Taxes on dividends and profits (IDU) – The taxpayer, generating event, scope, birth of the obligation, rates. UNIT III: EDGUR – IDU exclusions, transparent legal structures. The research was carried out with a qualitative approach, because the tax and accounting procedures of dividends and profits were studied according to Law 6380/19 of the Republic of Paraguay. The level of research used is descriptive, the information obtained allowed us to draw conclusions, to understand the scope of the Tax on dividends and profits on the distribution of dividends and profits of taxpayers affected by the Law. To understand the As a result, a questionnaire was proposed with open questions that were structured in a clear and precise way that verified all the points. The scope itself is that of the IDU, where accounting professionals say that the procedures for capitalization are after paying the tax and are distributed in money in kind and that the distribution is made after paying the tax.